EFFECTIVENESS OF POSTERIOR INTRAOSSEOUS ARTERY FLAP IN COVERAGE OF DORSAL HAND DEFECTS - Tauqeer, Zahra; Afridi, Riaz Ahmed Khan; Khan, Firdous (Khyber Journal of Medical Sciences, 2025)
Background: Hand injuries are a challenging issue, frequently encountered by orthopedic and plastic surgeons. These injuries often involve soft tissue defects that expose muscles, tendons, bones, and neurovascular structures. Prompt coverage of these defects is crucial to prevent infection and necrosis of the exposed tissues. Objective: To determine the effectiveness of the posterior intraosseous artery flap in coverage of dorsal hand defects. Methodology: This descriptive study was carried out at the Burns and Plastic Surgery Unit of Lady Reading Hospital Peshawar, from November 2022 to August 2024 after ethical approval. The sample size was determined to be 75 patients (95% CI, success rate 83.3%)8. The study included patients aged 18-60 years of either gender who presented with dorsal hand defects. Patients were followed up for up to a minimum of 6 months. Data was collected in Proforma and analyzed using SPSS 22. Results: The mean age was 39.13±12.06 years. The male-to-female ratio was 2.1:1. The average duration since trauma was 3.03±1.23 hours. The right hand was most frequently affected (61.3%). The most common mechanism was crush injury (38.7%), followed by degloving (26.7%). The overall flap success rate was 81.3% (Two-tailed p value 0.70 ± 0.045) indicating no significant difference between the observed flap success rate of 81.3% and the expected rate of 83%.8 Conclusion: The posterior interosseous artery flap is beneficial for covering dorsal hand defects due to its single-stage procedure and the ability to provide pliable coverage without the need to sacrifice any major vessels.